2014
DOI: 10.1016/j.fusengdes.2014.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of hydrogen isotope concentration in erbium oxide coatings

Abstract: Hydrogen isotope concentrations in erbium oxide coatings fabricated by filtered arc deposition and metalorganic decomposition have been investigated using nuclear reaction analysis and secondary ion mass spectroscopy. It was found that deuterium concentration in the coatings fabricated by filtered arc deposition was 300-500 atomic parts per million, whereas the deuterium concentration in the coating fabricated by metal-organic decomposition was approximately 2.0 × 10 4 atomic parts per million due to hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The results of permeation experiments and microstructure observation indicated that the deuterium permeation was dominated by grain boundary diffusion in the temperature range of 500-700 °C. This suggestion was verified by deuterium concentration in the coatings measured using nuclear reaction analysis (NRA) and nano-scale SIMS [292]. On the other hand, the hydrogen permeation through sintered Al O 2 3 tubes tested at higher temperatures (1200-1450 °C) showed that the dominant transport process was lattice diffusion [293,294].…”
Section: Influence Factors In Permeationmentioning
confidence: 81%
“…The results of permeation experiments and microstructure observation indicated that the deuterium permeation was dominated by grain boundary diffusion in the temperature range of 500-700 °C. This suggestion was verified by deuterium concentration in the coatings measured using nuclear reaction analysis (NRA) and nano-scale SIMS [292]. On the other hand, the hydrogen permeation through sintered Al O 2 3 tubes tested at higher temperatures (1200-1450 °C) showed that the dominant transport process was lattice diffusion [293,294].…”
Section: Influence Factors In Permeationmentioning
confidence: 81%
“…However, these coatings rely on defect-free layers and any pores or cracks are essentially short-circuit paths for hydrogen transport. For example, the permeability of SiC varies 5-6 orders of magnitude [147], and the PRF of Er 2 O 3 coatings was found to be inversely proportional to grain boundary density [148]. This relates to the degradation of permeation barriers in radiation environments where defects are formed.…”
Section: Tritium Permeation and Managementmentioning
confidence: 99%
“…Compared to Sample #2 of the F82H, the deuterium concentrations in the coatings were 1-3 orders of magnitude higher. In the previous studies of deuterium retention behavior on erbium oxide (Er2O3) coatings [6,13,14], it was considered that deuterium accumulated and/or diffuse along grain boundaries in the coatings. In this study, Y2O3 and ZrO2 coatings were polycrystalline, and thus deuterium would also 14 remain in grain boundaries of these two ceramic coatings.…”
Section: Deuterium Retention Behaviormentioning
confidence: 99%
“…Another critical problem is tritium inventory, which drastically varies fuel efficiency as permeation. Hydrogen isotope inventory in the TPB coatings has also been investigated in our previous studies [5,6]. These papers revealed that the amount of deuterium retention in ceramic coatings was much larger than that in steels.…”
Section: Introductionmentioning
confidence: 97%